2015
DOI: 10.1111/ane.12372
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of lacosamide as adjunctive therapy in refractory epilepsy

Abstract: Background Lacosamide (LCM) is a novel antiepileptic drug (AED) with potential benefit as adjunctive treatment in patients with partial‐onset seizures. As yet, limited information on cognitive effects of LCM is available, especially in real‐life settings. Aims In this open clinical prospective study, the cognitive effects of LCM were evaluated when used as adjunctive antiepileptic therapy in patients with refractory epilepsy. Methods We included 33 patients aged between 16 and 74 years (mean: 37 years). All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
2
13
0
5
Order By: Relevance
“…Overall, TEAEs reported during this trial were consistent with the known safety profile of LCM,25 and no new safety signals were detected. Recent data also indicate that adjunctive LCM does not affect information processing speed, the most sensitive function for cognitive side effect of AEDs, confirming observations in healthy volunteers 26, 27 …”
Section: Discussionsupporting
confidence: 71%
“…Overall, TEAEs reported during this trial were consistent with the known safety profile of LCM,25 and no new safety signals were detected. Recent data also indicate that adjunctive LCM does not affect information processing speed, the most sensitive function for cognitive side effect of AEDs, confirming observations in healthy volunteers 26, 27 …”
Section: Discussionsupporting
confidence: 71%
“…Our results are consistent with previous studies. IJff et al [7] examined 33 patients with refractory partial epilepsy in which lacosamide was added to their previous AED regimen. Two psychometric tools were used: the SIDAED and the Computerized Visual Searching Task (CVST).…”
Section: Discussionmentioning
confidence: 99%
“…Other data regarding mood/cognition have been limited to small prospective uncontrolled or retrospective studies. IJff et al [7] studied patients with refractory partial-onset epilepsy prospectively before and after lacosamide was added as adjunctive therapy. The authors reported that patients had increased subjective complaints but that, objectively, they did not do worse with lacosamide on a computerized task [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacosamide was shown to reduce cocaine‐induced elevations in reward function in rats, which is considered to be a common feature of manic episodes . It has also showed a more beneficial psychotropic profile than other antiepileptic drugs, especially regarding affective symptoms, and caused no impairment of cognitive abilities . However, its off‐label use is still limited.…”
mentioning
confidence: 99%